Analisis Determinan Pertumbuhan Ekonomi: Tingkat Pengangguran, Kemiskinan, dan Indeks Pembangunan Manusia di 34 Provinsi Indonesia - Ni Komang Gita Sukmasanti; Satarudin Satarudin; Nadia Nuril Ferdaus (Economic Reviews Journal, 2026)
Economic growth is an important indicator in assessing development success; however, its increase is not always followed by equal welfare distribution across regions. In Indonesia, disparities in unemployment, poverty, and the Human Development Index (HDI) still persist across 34 provinces during the 2020–2024 period. This condition indicates that economic growth has not been fully inclusive, making this study relevant to conduct. This study aims to analyze the effect of unemployment rate, poverty rate, and HDI on economic growth in 34 provinces of Indonesia, both partially and simultaneously. This research employed a quantitative approach using panel data and was analyzed through the fixed effect model. The results show that the unemployment rate and poverty rate have a negative and significant effect on economic growth, while HDI has a negative but insignificant effect. Simultaneously, all three variables have a significant effect on economic growth. These findings emphasize the importance of reducing unemployment and poverty in order to promote inclusive and sustainable economic growth.